5-Hydroxyindole-secreting rectal carcinoid tumour. Issue 5 (May 1972) - Murray-Lyon, Iain M.; Sandler, M.; Cheetham, H. D.; Watts, J. A. E.; Williams, Roger
Abstract : A patient with a 5-hydroxyindole-secreting rectal carcinoid tumour is described, the second on record. There was no clinical evidence of carcinoid syndrome. Prostaglandin-like substances were isolated from hepatic metastases.